Arthroscopic Superior Capsular Reconstruction for Massive Irreparable Rotator Cuff Repair - Burkhart, Stephen S. (Arthrosc Tech, 2016)
We have been performing arthroscopic superior capsular reconstruction (SCR) with acellular dermal allograft for almost 2 years. Our techniques are based on Mihata's original concept for SCR, in which he used fascia lata autograft. In this report, we describe our standard arthroscopic technique as well as 2 variations of a “zip-line” technique, which we have found particularly useful for large dermal allografts (grafts that are ≥40 mm in any dimension).